2013
DOI: 10.1371/journal.pone.0076437
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Leptin Antagonism in Ophthalmic Cell Models

Abstract: BackgroundEmerging evidence suggests that angiogenic and pro-inflammatory cytokine leptin might be implicated in ocular neovascularization. However, the potential of inhibiting leptin function in ophthalmic cells has never been explored. Here we assessed mitogenic, angiogenic, and signaling leptin activities in retinal and corneal endothelial cells and examined the capability of a specific leptin receptor (ObR) antagonist, Allo-aca, to inhibit these functions.Methods and ResultsThe experiments were carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…This study focuses on the angiogenic function of leptin and its involvement in ocular neovascularization. The leptin receptor (ObR) is expressed in vascular endothelial cells and studies in vitro demonstrated that leptin can induce angiogenic differentiation as well as proliferation and migration of endothelial cells, including cells of ophthalmic origin (Bouloumié et al, 1998 ; Sierra-Honigmann et al, 1998 ; Cao et al, 2001 ; Park et al, 2001 ; Anagnostoulis et al, 2008 ; Ferla et al, 2011 ; Garonna et al, 2011 ; Scolaro et al, 2013 ; Parrino et al, 2014 ; Adya et al, 2015 ). In mouse models, transgenic overexpression of the leptin gene ( ob ) potentiated ischemia-induced retinal neovascularization, while leptin deficiency due to ob inactivation, significantly reduced ocular angiogenesis, proving again the role of this cytokine in neovascularization (Suganami et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study focuses on the angiogenic function of leptin and its involvement in ocular neovascularization. The leptin receptor (ObR) is expressed in vascular endothelial cells and studies in vitro demonstrated that leptin can induce angiogenic differentiation as well as proliferation and migration of endothelial cells, including cells of ophthalmic origin (Bouloumié et al, 1998 ; Sierra-Honigmann et al, 1998 ; Cao et al, 2001 ; Park et al, 2001 ; Anagnostoulis et al, 2008 ; Ferla et al, 2011 ; Garonna et al, 2011 ; Scolaro et al, 2013 ; Parrino et al, 2014 ; Adya et al, 2015 ). In mouse models, transgenic overexpression of the leptin gene ( ob ) potentiated ischemia-induced retinal neovascularization, while leptin deficiency due to ob inactivation, significantly reduced ocular angiogenesis, proving again the role of this cytokine in neovascularization (Suganami et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that leptin is a potent mitogenic and angiogenic factor in retinal and corneal endothelial cells (Scolaro et al, 2013 ; Parrino et al, 2014 ). We have described that these leptin functions are associated with the modulation of the activity or expression of several signaling molecules involved in proliferation, inflammatory activity and angiogenesis, including the transcription factor STAT3, common kinases Ras, ERK1/2 and Akt, pro-inflammatory mediators and regulators COX2 and NF-κB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many other cell lines, adiponectin reduces leptin‐induced STAT3 phosphorylation and signaling . Thus, we selected two non‐tumor cell lines that are still stimulated by leptin addition together with STAT3 activation and this growth stimulation/STAT3 activation can be reversed by concomitant addition of Allo‐aca . Adiponectin protein inhibits the proliferation of BCE cells .…”
Section: Resultsmentioning
confidence: 99%
“…24 ADP355 reduces ERK1/2 activation in BC cells 10 similar to the effect of ObR antagonist peptides in both cancer and the endothelial cell models. 24,42 Leptin added at 15 nM increased BCE and RF/6A cell proliferation at 24 h by 21% and 26%, respectively (Table II). When the cells were concomitantly treated with 15 nM leptin and 100 nM Allo-aca, the cell growth was reduced to 13% (BCE) and 16% (RF/6A) compared to untreated controls (Table II).…”
Section: Optimization Of Adiponectin-derived Peptides 161mentioning
confidence: 98%